Public and Private Cults of Hygieia (Particularly Focusing on Crete) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
Aim of this article is a survey of the cults dedicated to Hygieia in public and private spheres. This is the occasion of analyzing the conception of health and Hygieia among the archaic poets, and the process by which Hygieia from personification became a deity. Also analyzed is the link of Hygieia with other deities or personifications, the symbolism of certain attributes and epithets in poetry and cult and the meaning of certain gestures. Particular attention is paid to Crete (especially Gortyna) and finally to the presence of Hygieia in baths and thermae.
Keywords: Cults; Greek archaic poets; Crete; Gortyna; baths and thermae